Hopf Bifurcation for the Prey-Predator Rosenzweig-MacArthur Model - Llibre, Jaume; Serantola, Leonardo (Journal of Applied Nonlinear Dynamics, 2026)
This paper studies the bifurcation of limit cycles for a specific predator-prey model called Rosenzweig-MacArthur, that presents persistent oscillations in the amount of individuals of the population from predator group and from the prey group. This model uses a Holling Type II function response. The averaging theory of third order allows to investigate the Hopf bifurcation that exhibits this model, providing an analytical approximation of the bifurcated periodic orbit and its kind of stability.